KAJIAN PENGENDALIAN PENYAKIT LAYU BAWANG MERAH DENGAN BIOPESTISIDA DI SULAWESI TENGGARA - Muh Asaad; Rusdi Rusdi; Agussalim Agussalim (Balai Besar Pengkajian dan Pengembangan Teknologi Pertanian, 2020)
The Study of Shallot Wilt Disease with Biopesticide in South Sulawesi. The study aimed to obtain an effective biopesticide to controlshallot wilt disease which was conducted in March to July 2017 in Andowengga Village, Poli-Polia Sub-district, East Kolaka District, Southeast Sulawesi. The study used randomized block design (RBD) with 4 (four) treatments namely (1) biopesticide Trichoderma spp 15 kg/10 m2+organic fertilizer 100 kg/10 m2, (2) Gliocladium spp 100 g/10 m2+ organic fertilizer 100 kg/10 m2, (3) Bacillus sp1 litre/100 liter/10 m2+ organic fertilizer 100 kg/10 m2 and (4) control (organic fertilizer) 100 kg/10 m2 with 5 (five) replications. The variable observed were potential of biopesticide suppression of wilt disease, the intensity of the wilt disease as well as vegetative growth and shallot production. The results of the study showed the Trichoderma, Gliocladium and Bacillus biopesticides can control wilt in shallot plants. The treatmentof Bacillus biopesticides was able to control wilt with a level of suppression (efficacy) of 50,70% in the vegetative growth phase, 24% in the tuber formation phase andto provide higher productivity compared to the other two treatments which was 125 kg/10 m2 or equivalent to 1.25 t/ha in local specific condition in Southeast Sulawesi.Keywords: shallot, wilt diseases, biopesticides, productivity ABSTRAKKajian bertujuan mendapatkan biopestisida yang efektif mengendalikan penyakit layu pada bawang merah yang telah dilaksanakan pada bulan Maret sampai Juli 2017 di Desa Andowengga, Kecamatan Poli-Polia, Kabuapten Kolaka Timur. Kajian menggunakan rancangan acak kelompok (RAK) dengan 4 (empat) perlakuan yaitu (1) Biopestisida Trichoderma spp 15 kg/10 m2 + pupuk organik 100 kg/10 m2 (2) Gliocladium spp 100 g/10 m2 + pupuk organik 100 kg/10m2, (3) Bacillus sp 1 l/100 l/10 m2 + pupuk organik, 100 kg/10 m2, dan (4) Kontrol (pupuk organik) 100 kg/10 m2 sebanyak 5 (lima) ulangan. Peubah yang diamati mencakup potensi penekanan biopestisida terhadap penyakit layu, intensitas serangan penyakit layu, pertumbuhan vegetatif, dan produksi bawang merah. Hasil kajian menunjukkan biopestisida Trichoderma, Gliocladium, dan Bacillus dapat mengendalikan penyakit layu pada tanaman bawang merah. Perlakuan biopestisida Bacillus mampu mengendalikan penyakit layu dengan tingkat penekanan (efikasi) sebesar 50,70% pada fase pertumbuhan vegetatif, 24% pada fase pembentukan umbi, dan memberikan produktivitas bawang merah yang lebih tinggi dibandingkan dua perlakuan lainnya yakni sebesar 125 kg/10 m2 atau setara 1,25 t/ha pada kondisi spesifik lokasi Sulawesi Tenggara.Kata kunci: bawang merah, penyakit layu, biopestisida, produktivitas